Research on the movement law of overlying strata and mine pressure behavior in fully mechanized top-coal caving mining under goaf - Dong, Fa; Wang, Shuai; Jing, Gang; Zhang, Wenzhou; Nan, Hua; Wang, Laolao (Frontiers in Earth Science, 2025)
During the mining of the lower coal seam under goaf, strong ground pressure behavior and severe roadway deformation occur, affecting normal mining. This study integrated theoretical analysis, laboratory tests, numerical simulation, and field application to explore overlying strata structure/stability, movement and mine pressure behavior laws, and ground pressure sudden change countermeasures in fully mechanized top-coal caving mining under goaf. Results showed that after upper coal seam mining, a stable “masonry beam” formed in the upper key stratum, with floor stress disturbance depth ∼60 m and fractured zone depth ∼7.47 m. Lower coal seam mining initially showed layered overlying strata caving; goaf connection activated upper goaf overlying strata, destabilized the “pressure arch”, and caused shear failure with a “stepped rock beam” structure. Taking goaf connection as the boundary, ground pressure exhibited strong/weak periodic weighting. Weak weighting (larger interval, lower intensity) resulted from lower key stratum periodic fracture; strong weighting (smaller interval, higher intensity) occurred when two coal seams’ damaged areas connected, transferring overlying strata weight to the lower face. When the seam height ratio <5.70 (mining height >8 m), damaged areas connected, causing intense strong weighting. A ratio of 5.70–11.40 (mining height 5–8 m) led to slight weighting intensity difference. A ratio >11.40 (mining height <5 m) prevented connection and ground pressure sudden change. The targeted control scheme achieved good effects, with no support crushing and improved roadway convergence.